Entrepreneurial leadership practices and school innovativeness - Lope Pihie, Zaidatol Akmaliah; Asimiran, Soaib; Bagheri, Afsaneh (Education Association of South Africa, 2014)
Entrepreneurial leadership, as a distinctive type of leadership required for dealing with challenges and crises of current organizational settings, has increasingly been applied to improve school performance. However, there is limited research on the impact of school leaders’ entrepreneurial leadership practices on school innovativeness. The main purpose of this study is to identify the relationship between principals’ entrepreneurial leadership practices and school innovativeness through the teachers’ perspectives. The participants included 294 Malaysian secondary school teachers in Selangor, Malaysia. A questionnaire containing 64 items (50 items on school principals’ entrepreneurial leadership practices and 14 items on school innovativeness) was utilized. An analysis of the data indicates that teachers perceive entrepreneurial leadership as highly important for school principals. However, the principals practise it moderately. Furthermore, this study found a significant correlation between teachers’ perceptions of school principals’ entrepreneurial leadership practices and school innovativeness. Implications of the findings for developing school principals’ entrepreneurial leadership and school innovativeness are discussed.